THU0174 Drug retention of tofacitinib versus biologic antirheumatic agents in rheumatoid arthritis: observational data from the swiss scqm registry. (15th June 2017) - Finckh, A; Herzog, L; Scherer, A; Dudler, J; Moeller, B; Ciurea, A; Mueller, R; Hasler, P; Exer, P; Muehlenen, I von; Kyburz, D; Gabay, C; et al.
Abstract : Background: The oral Janus kinase inhibitor tofacitinib (Tofa) was licensed in Switzerland in 2013 for the treatment of moderate to severe rheumatoid arthritis (RA) patients having failed methotrexate. Besides Tofa, rheumatologists in Switzerland have the choice between 7 alternative bDMARDs licensed with similar indications, including 5 TNF inhibitors (TNFi) and 2 bDMARDs with other modes of action (OMA-bDMARDs). Objectives: To compare the drug retention rate of three alternative treatment options licensed with a similar indications, namely Tofa, TNFi and OMA-bDMARDs, using data from the Swiss registry. Methods: This is an observational cohort study within the Swiss Clinical Quality Management registry (SCQM). All therapies with Tofa, TNFi, and OMA-bDMARDs initiated in adult RA patients between August 1, 2013 and Dec 1, 2016 were considered. The exposure of interest was treatment with Tofa vs TNFi and vs OMA-bDMARDs (Abatacept or Tocilizumab). The primary outcome was drug retention defined as the time from initiation to discontinuation of treatment. We used Kaplan Meier curves to display drug retention and Cox proportional hazard models stratified by seropositivity to analyze the hazard for treatment discontinuation. We adjusted for potential confounders, including gender, age, disease duration, seropositivity, BMI, smoking status, DAS28-CRP and the total number of previous bDMARDs. We applied multiple imputation to account for missing baseline covariate data. Results: A total of 1996 therapies were initiated during the study period (376 Tofa, 928 TNFi, 692 OMA-bDMARDs). Some differences in disease and treatment characteristics existed between the 3 groups, in particular TNFi tended to be used in patients with fewer previous bDMARDs experience, younger age and shorter disease duration. The crude overall drug retention was similar between the 3 three drug groups ( p =0.24) (Figure 1 A). The adjusted analysis demonstrated a slightly higher hazard of drug discontinuation with TNFi compared to Tofa [HR 1.27 (95% CI: 1.02 – 1.57, p=0.03)], while no difference was observed for OMA-bDMARDs and Tofa [HR 1.03 (95% CI: 0.83 – 1.28, p=0.76)] (Figure 1 B). Complete case results were consistent with results using multiple imputation of baseline covariates. Other variables significantly associated with drug discontinuation were a higher number of previous bDMARDs ( p <0.001) and increasing BMI values ( p= 0.03), while combination therapy with sDMARDs tended to decrease discontinuation ( p =0.08) Conclusions: The results of this observational study suggest that Tofa is a valuable alternative to treatment options in RA, with Tofa drug retention at least comparable to other available bDMARDs. Acknowledgements: Disclosure. Investigator Initiated Research grant supported by Pfizer. Disclosure of Interest: A. Finckh Grant/research support from: BMS, Speakers bureau: Abbvie, BMS, Pfizer, Roche, UCB, L. Herzog: None declared, A. Scherer: None declared, J. Dudler: None declared, B. Moeller: None declared, A. Ciurea: None declared, R. Mueller: None declared, P. Hasler: None declared, P. Exer: None declared, I. von Muehlenen: None declared, D. Kyburz: None declared, C. Gabay: None declared, P. Zufferey: None declared